Towards Clinical Bioinformatics: Advancing Genomic Medicine with Informatics Methods and Tools - Knaup, P.; Ammenwerth, E.; Brandner, R.; Brigl, B.; Fischer, G.; Garde, S.; Lang, E.; Pilgram, R.; Ruderich, F.; Singer, R.; Wolff, A. C.; Haux, R.; Kulikowski, C. (Methods of Information in Medicine, 2004)
Objectives: To summarize the challenges facing clinical applications in the light of growing research results in genomic medicine and bioinformatics.Methods: Analysis of the contents of the Yearbook of Medical Informatics 2004 of the International Medical Informatics Association (IMIA).Results: The Yearbook of Medical Informatics 2004 includes 32 articles selected from 22 peer-reviewed scientific journals. A special section on clinical bio-informatics highlights recent developments in this field. Several guest editors review the promises and limitations of available methods and resources from biomedical informatics that are relevant to clinical medicine. Integrated data and knowledge resources are generally regarded to be central and key issues for clinical bioinformatics. Further review papers deal with public health implications of bioinformatics, knowledge management and trends in health care education. The Yearbook includes for the first time a section on the history of medical informatics, where the significant impact of the Reisensburg protocol 1973 on international health and medical informatics education is examined.Conclusions: Close collaboration between bio-informatics and medical informatics researchers can contribute to new insights in genomic medicine and contribute towards the more efficient and effective use of genomic data to advance clinical care.
Keywords: Medical informatics; International Medical Informatics Association; clinical bioinformatics; yearbook